Pulmonary Manifestations of SARS Co V 2 Infection in Mild/Severe Patients - Jalili, Zahra; Jalili, Hamid Reza; Nazarinejad, Nooshin; Hajikhani, Bahareh; Yazdani, Shahrooz; Bahonar, Sara; Sameni, Fatemeh (Novelty in Biomedicine, 2023)
The coronavirus disease 2019 (COVID-19) caused viral pneumonia in Wuhan City in China in December of 2019. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily targets the lungs with severe hypoxia, which usually results in death. COVID-19 is highly heterogeneous regarding severity, clinical phenotype, and more importantly, global dispersal. The respiratory system in all aspects such as respiratory airways, endothelium of pulmonary vessels, conducting airways, the alveoli, neuromuscular breathing structure, and pulmonary circulation are affected by this virus. A comprehensive concept of the source and dynamic action of the SARS-CoV-2 and the possible causes of heterogeneity in COVID-19 is required for predicting and managing the illness in acute and chronic stages of the pulmonary sign.